An Untranslatable Hong Kong story: Wong Bik-wan’s “Nausea” - Yee Kwan Wong (Writing Chinese: A Journal of Contemporary Sinophone Literature, 2023)
In this article, I address Leung Ping-kwan’s oft-cited question “Why is the story of Hong Kong so difficult to tell?” from the angle of language. Owing to its cultural plurality and changing historical circumstances, Hong Kong is constantly searching for words to express its identities. This is encapsulated in “untranslatability”, the idea that new meanings are generated in the interminable exchanges between propositions, which is exemplified in Wong Bik-wan 黃碧雲’s “Nausea [au2 tou3] 嘔吐)” (1994). An homage to Jean-Paul Sartre’s La Nausée (1938), this short story demonstrates Hong Kong’s multilingualism, as it features characters from diverse ethnic, cultural, and linguistic backgrounds. Interweaving the foreign and local, “Nausea” foregrounds the conflicts between these characters, which are mediated through linguistic and cultural translations. Moreover, through the interpersonal translation of “vomiting”, dialogic sympathy across differences becomes possible. Lastly, set in 1984, the year when the Sino-British Joint Declaration was signed, “Nausea” portrays Hong Kong in a state of political precarity and translates its citizens’ profound identity confusion into an existential crisis. As such, “Nausea” re-interprets Sartre’s existentialist literature through a (post)colonial, gendered perspective, and compels its readers to reflect on Hong Kong’s identity after British colonialism. Ultimately, (un)translation not only animates the ever-evolving meanings in a literary text, but also has ramifications on the city’s present and future: it shows that “Hong Kong” is still formulating a language for its self-expression in an ongoing process of storytelling.